Kepemimpinan Transformasional Terhadap Kinerja Karyawan Dimediasi Budaya Organisasi Dan Motivasi - Ahmad Qoni Dewantoro (Jurnal Manajerial, 2023)
Background – Currently, company leaders, besides being tasked with assessing the performance of their employees, also need transformational abilities because transformational management has been proven to increase productivity in the workplace. Aim – The aims of this study were to determine the effect of transformational leadership on employee performance, both directly and indirectly through organizational culture and motivation. Design / methodology / approach – The research method refers to a positivism approach with quantitative methods, using 77 participants as a sample for filling out the questionnaire, while Path Analysis is used to analyze the data that has been collected. Findings – This study refutes the notion that transformative leadership has a direct impact on employee performance. By inspiring their employees, transformational leaders have an indirect effect on performance. Furthermore, the characteristics of organizational culture are not significantly influenced by transformative leadership. Conclusion - Transformational leaders can use various sources of inspiration to improve performance. As a result, leaders play an important role in increasing employee motivation. Research Implication - The findings of this study have managerial significance because a shift in leadership style is necessary to improve performance. These results highlight the value of transformative and motivational leadership in enhancing workplace performance. Limitations – This research only collects data from one banking company, then the characteristics of the sample have different characteristics from the others, where the bank as a sample is owned by the regional government so that it may be different if the data is taken based on ownership and also different banks.